The effect of economic growth and energy consumptions towards carbin dioxide emissions for developed and developing countries in Asia - Thanes Raj, a/l Padmanathan (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The general objective of this paper is to examine the relationships between carbon dioxide emissions, economic growth and energy consumptions for developed (Singapore and Japan) and developing (Indonesia and Thailand) countries in Asia by using times series data for the period 1971-2013 at the annual data. The unit root tests, cointegration test and Vector Error Correction Model test are conducted in this study. This study found that the cointegration relationship exists in Japan, Indonesia and Thailand only. Furthermore, energy consumption is identified to be a significant variable in determining the carbon dioxide emission for Japan, Indonesia and Thailand. Besides, the square of RGDP is included to identify the existence long run relationship in Environmental Kuznets Curve (EKC), which results in an inverted U-curve relationship for Japan and Thailand, whereas Indonesia is a U-curve relationship. Economic growth play an important role in determines causality for Indonesia, Thailand and Singapore. Overall, to reduce carbon dioxide emission and to increases energy efficiency, sustainable conservation policies need to be implemented to abate unnecessary energy wastage thus increases economic growth.